The Efficacy and Safety of a 755-nm Picosecond Laser in the Treatment of Physiologic Lip Hyperpigmentation in Thai Patients - Ng J.N.C. (2023)
BACKGROUNDPhysiologic lip hyperpigmentation is a common aesthetic concern, especially in Southeast Asia. There is limited data on the application of the picosecond laser for this condition.OBJECTIVETo evaluate the efficacy and safety of using a 755-nm picosecond laser in the treatment of physiologic lip hyperpigmentation.METHODSTwenty healthy patients with physiologic lip hyperpigmentation received 5 bi-weekly treatments with a 755-nm picosecond laser using a 6-mm spot size, fluence of 0.71 J/cm2 at 5 Hz. Subjective and objective evaluation on the improvement of lip hyperpigmentation were obtained at baseline, 2 weeks after each treatment and at 1, 3, and 6 months after the final treatment. Patient self-assessment, pain score, and adverse reactions were also recorded.RESULTSAll patients completed the study and attended all follow-ups. Most (52.6%) patients presented with moderate clinical improvement at 6-month follow-up. The average melanin index decreased significantly after the fourth treatment (p =.048) and at 1-month follow-up (p =.026). More than half the patients (70%) reported moderate-to-marked improvement at 6-month follow-up. Only 1 patient presented with a transient adverse reaction of lip edema.CONCLUSIONThe 755-nm picosecond laser is safe and effective for the treatment of physiologic lip hyperpigmentation in Thai patients.